Wpływ Wrocławskiego Obszaru Metropolitalnego na otoczenie - Krześ, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
Metropolises are a force that propels the growth of the local economy, clusters well educated individuals and attracts investors as well as innovations. By creating a network of international relations metropolises hold a dominant position within their country. They are also the centers of development for the knowledge society and the places where innovations emerge and diffuse. This leads to a number of changes which can have a positive impact, but may also bear negative consequences. The paper below is an attempt to show, on the example of Wrocław, if and how a city affects the areas around it.
Keywords: Wrocław; lokalna gospodarka